2011
DOI: 10.1097/ijg.0b013e3181e3d2da
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of Plateau Iris Configurations Between Angle-closure Glaucoma and Open-angle Glaucoma Using Ultrasound Biomicroscopy

Abstract: Eyes with OAG had a higher rate of plateau iris configurations than expected. Longitudinal studies to evaluate plateau iris height are required to determine its significance in the pathogenesis of angle-closure glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…Specifically, those eyes with shorter AL or higher SE were predisposed to higher prevalence of PIC, which makes sense mechanistically. Previous studies done in patients with PIC7 13 15 21 showed similar results to our current study, where plateau iris syndrome eyes were found to be more likely to be non-myopic and have shorter AL. In fact, based on our analysis, emmetropic and hyperopic eyes are 2.82 times more likely to have PIC when compared with myopic eyes, suggesting that myopia might be a protective factor against PIC formation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, those eyes with shorter AL or higher SE were predisposed to higher prevalence of PIC, which makes sense mechanistically. Previous studies done in patients with PIC7 13 15 21 showed similar results to our current study, where plateau iris syndrome eyes were found to be more likely to be non-myopic and have shorter AL. In fact, based on our analysis, emmetropic and hyperopic eyes are 2.82 times more likely to have PIC when compared with myopic eyes, suggesting that myopia might be a protective factor against PIC formation.…”
Section: Discussionsupporting
confidence: 91%
“…PIC-associated anterior chamber characteristics include a normal central anterior chamber depth (ACD), a flat iris plane, an iris root that angles sharply forward, and anteriorly positioned or large ciliary processes 6–9. After PIC was initially described,10 11 some researchers reported its prevalence among PACG patients as 30% in Singapore,12 30% in India,13 47.8% in China14 and 37.0% in Japan 15. In addition, recent research also reported PIC in POAG 16.…”
Section: Introductionmentioning
confidence: 99%
“…The author mentions that there were significant differences in the duration of glaucoma treatment among the 3 groups, which may have contributed to success rates. The article cited by the authors to corroborate this was published in 1994 by Broadway et al 1 However, 2 largescale multicenter studies (CAT 152 trial, 2 n = 726 and National survey of trabeculectomy 3 in the United Kingdom, n = 1240) published more recently have not demonstrated a consistent relationship between duration of glaucoma and trabeculectomy outcomes. Possible reasons could be that medical management of glaucoma has come a long way over the past decade and the newer drugs do not alter the conjunctival cytology as much as b-blockers or miotics.…”
supporting
confidence: 64%
“…14,16 However, the diagnostic criteria for plateau iris are not well defined. 14,15,[17][18][19] Using their diagnostic criteria in UBM, Kumar et al 14,20 found plateau iris ( ‡2 quadrants) in 32.4% of PACG eyes after patent LPI. We used criteria similar to those of Kumar et al 14,20 and found plateau iris ( ‡2 quadrants) in only 9.7% (13 of 134) subjects.…”
Section: Discussionmentioning
confidence: 99%